First case reported of bronchoconstriction in feline aelurostrongylosis by using barometric whole-body plethysmography - GARCÍA-GUASCH, L.; MANUBENS, J.; LAPORTA, M.; CARRETÓN, E.; MONTOYA-ALONSO, J. A. (Journal of the Hellenic Veterinary Medical Society, 2018)
Symptomatic cats infected by Aelurostrongylus abstrusus show non-specific and respiratory clinical signs, often misdiagnosed as other diseases more prevalent among feline population, such as allergic respiratory disease or heartworm associated respiratory disease (HARD). Clinical signs are due to the pulmonary inflammatory response caused by the eggs shed by the adult females and the migration of the first-stage larvae up the bronchial tree. Barometric whole-body plethysmography (BWBP) is a non-invasive pulmonary function test that allows a dynamic study of breathing patterns by placing the patient within an unrestrained Plexiglas chamber. This is the first report that determines the degree of bronchoconstriction caused by A. abstrusus infection in a cat by using BWBP, showing an increase of baseline measurements of bronchoconstriction indexes (Enhanced pause and Pause) in response to severe bronchial reactivity, a consequence of the airway inflammation caused by the presence of A. abstrusus.